Effect of patient education on surgical site infections rates: a systematic review of the literature - Michail, Koralia; Tsitsi, Theologia; Charalambous, Marianna (My University, 2024)
The present systematic review aimed to investigate the effectiveness of patient engagement through education and empowerment on surgical site infection (SSI) rates. Included studies involved adult patients undergoing surgical procedures with any educational intervention, aiming at patient engagement/empowerment, compared to no educational interventions or usual therapy. The information sources used were Web of Science, PubMed and Scopus, from 2013 until 2023. The Joanna Briggs Institute tool was used to assess the risk of bias, whereas our results were synthesized in a narrative form according to the research questions, due to the included studies’ heterogeneity. A total of ten studies were included with 9236 participants all of whom were clinic patients. Eight studies included educational interventions as part of prevention bundles. All studies demonstrated a reduction on SSI rates, following the intervention, even though no study scored high on quality assessment. The findings highlighted the added value of patient education in conjunction with the application of prevention measures. Patient empowerment through education encourages active patient participation in their care, increases patient satisfaction and, ultimately, improves the quality of provided care. The need for more high-quality studies emerged, which will focus on patient engagement to further elucidate its role in SSI prevention.
Keywords: Patient education; SSIs; Patient engagement; Wound infection